The situation comedy “Modern family” as a mirror of American family moral values = Bộ phim hài kịch tình huống “Gia đình hiện đại” và các giá trị đạo đức gia đình Mỹ - Trần, Thu Trà (2021)
Situation comedy is one important artifact that offers valuable understanding about a culture with in-depth investigation. Scholars have been studying to see how ideologies are reflected in sitcoms and whether members of the society behave accordingly to those values and ideologies and confirm their sense of belonging to that culture. This study applies textual analysis approach with an emphasis on family moral values to analyze the Emmy award-winning sitcom, Modern Family. The program’s overwhelming success among audiences as well as critics explains the wide scholarly attention it has earned. This study answers the question, “In what ways the sitcom Modern Family mirror the moral values of family cultures in the US?” The textual analysis revealed that the show does not exhaustively portray all of the four family cultures according to the categorization of Bowman et al. (2012). Additionally the portrayals in this series contain certain inconsistencies as a result of the stereotypical nature of sitcoms and dominant ideologies about gender roles in the family.